The Association Between Preoperative Anxiety and Pain Severity, Opioid Requirement, Neutrophil-to-Lymphocyte Ratio, and Postoperative Blood Glucose After Gynecologic Laparotomy at Ngoerah Hospital - Fivilia Anjelina Bora; Dewa Ayu Mas Shintya Dewi; I Putu Kurniyanta; Tjokorda Gde Agung Senapathi; I Made Gede Widnyana; Putu Pramana Suarjaya; I Gusti Ngurah Mahaalit Aribawa; Tjahya Aryasa EM; Pontisomaya Parami; Otniel Andrians Labobar (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: We assessed whether preoperative anxiety is associated with postoperative pain severity, opioid requirement, neutrophil-to-lymphocyte ratio (NLR), and blood glucose after gynecologic laparotomy. Methods: Prospective cohort at Ngoerah Hospital (May to June 2025). Anxiety was measured preoperatively with APAIS and categorized as non-anxious, mild, moderate, or severe. Outcomes were NRS pain at 6, 12, and 24 hours, total fentanyl in the first 24 hours, and NLR and blood glucose at 6 hours postoperatively. Multivariable analysis used MANCOVA (99% confidence intervals). Result: Fifty-four patients were included (mean age 41.78 ± 10.58 years). Anxiety distribution was 46.3% non-anxious, 25.9% mild, 24.1% moderate, and 3.7% severe. Higher anxiety was associated with higher NRS at 6 hours (B 0.842; 99% CI 0.475 to 1.209; p < 0.001), 12 hours (B 0.381; 0.247 to 0.515; p < 0.001), and 24 hours (B 0.158; 0.048 to 0.269; p = 0.048). Anxiety was associated with higher 24-hour fentanyl requirement (B 147.8 microg; 99% CI 124.062 to 171.651; p < 0.001), higher postoperative NLR (B 4.31; 99% CI 0.609 to 8.027; p = 0.024), and higher postoperative blood glucose (B 19.4 mg/dL; 99% CI 7.912 to 30.912; p = 0.001). Conclusions: Higher preoperative anxiety was independently associated with worse pain, greater opioid requirement, and higher postoperative NLR and blood glucose after gynecologic laparotomy.